3D lightweight double arrow-head plate-lattice auxetic structures with enhanced stiffness and energy absorption performance. (15th June 2022) - Guo, Meng-Fu; Yang, Hang; Ma, Li
Abstract: In lightweight engineering, higher specific stiffness and strength for low-density are constant quests, additively-manufactured auxetic truss-lattices have attracted great attentions due to their outstanding and designable mechanical properties. Recent advances revealed that the novel family of plate-lattices can enhance the stiffness and energy absorption capacity compared to truss-lattices. In this study, three types of novel 3D double arrow-head plate-lattice (DAPL) auxetic structures are proposed based on the polygon tessellations of 3D double arrow-head truss-lattice (DATL) structures. The compression tests are carried out on 3D printed plate-lattice structures to validate the finite element analysis and the influences of geometrical parameters on elastic constants are also investigated numerically. The results indicate that the 3D DAPL structures present auxetic behavior with enhanced stiffness, and the geometrical tessellation mode has no significant effect on specific stiffness for both 3D DATL and DAPL structures. The quasi-static crushing responses of 3D DAPL and DATL structures are studied and reveal that the plate-lattices can significantly improve the quasi-static energy absorption performances compared with truss-lattices for the same relative density. Finally, the low-velocity impact tests are performed on 3D DAPL structures and the results reveal that 3D DAPL have good impact resistance compared with other lattice structures for low densities. This paper combines the concept of plate-lattice with auxetic mechanism which will provide the guidance for the functional applications of lightweight materials.